Red Cabbage Juice Decreases Oxidative Stress in Hyperuricemia Model Rats - Muhammad Abdul Rauf; Budiyanti Wiboworini; Paramasari Dirgahayu (Universitas Aisyah Pringsewu, 2023)
Serum uric acid levels are recognized to be a substantial risk factor for developing oxidative stress-related illnesses. Red cabbage has the largest concentration of anthocyanins of any antioxidant, which contributes to oxidative stress. This study aimed to see how anthocyanins in red cabbage juice affected MDA levels in hyperuricemia model rats at different dosages and times of the intervention. A Randomized Complete Design was used to create a before and post-test group research design with 24 male Sprague-Dawley rats aged 10-12 weeks classified into four groups, the Control Group (KN) and the Treatment Group (P1-3). KN rats received standard feed, whereas P1-3 received a regular meal and dosages of red cabbage juice of 1.8, 3.6, and 7.2 ml/200g BW for 28 days. Uric acid levels are measured before and after induction, whereas MDA levels are measured before the installation, after induction (Day 0), on Day 14, and on Day 28. Data analysis was performed utilizing the One Way Anova test, Repeated Measured ANOVA, and a mixed design. Statistical testing revealed that dosage and intervention duration differences significantly lowered MDA levels in all treatment groups (p less than 0.05). On day 28, the red cabbage juice intake of 7.2 ml/200grBB returned MDA levels to normal. Abstrak: Peningkatan asam urat serum diketahui menjadi risiko utama terkait perkembangan penyakit akibat stres- oksidatif. Kubis merah mengandung antosianin paling tinggi diantara jenis antioksidan lain yang berperan terhadap keadaan oksidatif stress. Tujuan penelitian ini untuk mengetahui pengaruh antosianin dari jus kubis merah dengan variasi dosis dan lama waktu intervensi terhadap penurunan kadar MDA tikus model hiperurisemia. Penelitian Pre and post-test group esign dengan Rancangan Acak Lengkap menggunakan 24 tikus jantan Sprague-Dawley umur 10-12 minggu dibagi menjadi 4 kelompok yaitu Kelompok kontrol (KN) dan Kelompok Perlakuan (P1- 3). Tikus KN diberi pakan standart sedangkan P1-3 diberi pakan standart ditambah jus kubis merah dosis 1.8, 3.6, 7.2 ml/200g BB selama 28 hari. kadar asam urat dipantau sebelum dan setelah induksi, untuk kadar MDA dipantau sebelum Induksi, setelah induksi per Hari ke0, Hari ke 14 dan Hari Ke 28. Data dianalisi menggunakan uji One Way ANOVA, Repeated measured ANOVA dan mix design. Hasil uji statistik menjelaskan variasi dosis dan lama waktu intervensi terbukti nyata menurunkan kadar MDA pada semua kelompok perakuan (p kurang dari 0,05). Kesimpulannya jus kubis merah dosis 7,2 ml/200grBB mampu menurunkan kadar MDA mencapai batas normal pada hari ke 28.